Healthcare Providers' Experiences as Arts-Based Research Participants: "I Created My Story About Disability and Difference, Now What?". Issue 4 (December 2019) - Montgomery, Phyllis; Mossey, Sharolyn; Rice, Carla; McCauley, Karen; Chandler, Eliza; Changfoot, Nadine; Underhill, Angela
Little is known about the experiences of healthcare providers as research participants in qualitative studies employing methods that encourage disclosure of their own disabilities. In this paper, we describe the experiences and implications of creating personal stories of disability and difference for healthcare provider participants in an arts-based study. The study design is a supplementary secondary analysis of a subset of data from a larger study focused on transforming negative concepts of disability and difference entitled, Mobilizing New Meanings of Disability and Difference: Using Arts-Based Approaches to Advance Healthcare Inclusion for Women with Disabilities. This supplementary study explores the experiences and perspectives of 17 healthcare provider participants who completed semi-structured interviews following creation of a multi-media story about their experience of disability or difference. Using creative non-fiction methods, two narrative streams are identified about healthcare provider experiences and the impacts of participating. The first addresses shared positive experiences about the research. The second entails more ambivalent reflections on their involvement as participants. The tension between the two experiences generates considerations to forward a mutually beneficial alliance to disrupt ableist understandings in healthcare and reveals new meanings of disability that are agential and integral to the stories and storytellers themselves.